Spiro‐Bicyclic Bisborane Catalysts for Metal‐Free Chemoselective and Enantioselective Hydrogenation of Quinolines - Li, Xiang; Tian, Jun‐Jie; Liu, Ning; Tu, Xian‐Shuang; Zeng, Ning‐Ning; Wang, Xiao‐Chen (Angewandte Chemie International Edition, 2019)
A new series of spiro‐bicyclic bisborane catalysts has been prepared by means of hydroboration reactions of C2‐symmetric spiro‐bicyclic dienes with HB(C6F5)2 and HB(p‐C6F4H)2. When used for hydrogenation of quinolines, these catalysts give excellent yields and enantiomeric excesses, and show turnover numbers of up to 460. The most attractive feature of these metal‐free hydrogenation reactions was the broad functional‐group tolerance, making this method complementary to existing methods for quinoline hydrogenation. B,B bicycles: A series of C2‐symmetric spiro‐bicyclic bisboranes has been prepared. These bisboranes demonstrate highly effective and selective asymmetric hydrogenation of quinolines. The exceedingly broad functional‐group tolerance allows access to various enantioenriched and functionalized tetrahydroquinilines, which are inaccessible by previous methods using either borane or transition‐metal catalysts.